Role of Low Molecular Weight Polymers on the Dynamics of Silicon Anodes During Casting. Issue 11 (5th May 2021) - Burdette‐Trofimov, Mary K.; Armstrong, Beth L.; Murphy, Ryan P.; Heroux, Luke; Doucet, Mathieu; Trask, Stephen E.; Rogers, Alexander M.; Veith, Gabriel M.
Abstract: This work probes the slurry architecture of a high silicon content electrode slurry with and without low molecular weight polymeric dispersants as a function of shear rate to mimic electrode casting conditions for poly(acrylic acid) (PAA) and lithium neutralized poly(acrylic acid) (LiPAA) based electrodes. Rheology coupled ultra‐small angle neutron scattering (rheo‐USANS) was used to examine the aggregation and agglomeration behavior of each slurry as well as the overall shape of the aggregates. The addition of dispersant has opposing effects on slurries made with PAA or LiPAA binder. With a dispersant, there are fewer aggregates and agglomerates in the PAA based silicon slurries, while LiPAA based silicon slurries become orders of magnitude more aggregated and agglomerated at all shear rates. The reorganization of the PAA and LiPAA binder in the presence of dispersant leads to a more homogeneous slurry and a more heterogeneous slurry, respectively. This reorganization ripples through to the cast electrode architecture and is reflected in the electrochemical cycling of these electrodes. Abstract : Dispersant effects on silicon slurries : The structure of silicon electrode slurries with poly(acrylic acid) or lithium neutralized poly(acrylic acid) binder, with and without dispersant, were studied under shearing conditions, mimicking slurry casting conditions, using rheology coupled ultra‐small angle neutron scattering.